Shaking Table Test on Seismic Response of Tunnel-Soil Surface Structure System considering Soil-Structure Interaction - Yantao Li; Ye Tian; Jinhui Zong (Shock and Vibration)
With the increasing number of underground structures traversing the surface structure, the surface and underground structures interact with each other during earthquakes, thus affecting the seismic response of the interaction system. Based on this idea, the dynamic interaction system of a tunnel-soil-surface structure is designed. The seismic responses such as acceleration, strain, and interlayer displacement angle are analyzed, and the vibration characteristics and laws of the interaction system under different seismic loads are studied through the shaking table test. The results show that the type of seismic wave has a significant impact on the seismic response of the system, in which the dynamic response of the surface structure and soil is more sensitive to the seismic wave with rich low-frequency components. The acceleration response of soil near the tunnel-surface structure area is stronger than that of soil far away from the interaction area. During earthquakes, the maximum strain of the deep tunnel appears in the region of 45° between the two sides of the lining and the vertical symmetry axis, whereas the maximum strain of the shallow tunnel close to the surface structure is different from that of the deep tunnel. For the surface structure, with the input peak acceleration increasing, the weak layer of the surface structure moves down, and the interlayer displacement angle of the middle and lower layers is significantly larger. The research results have certain reference significance for exploring the seismic response law of a tunnel-soil-surface structure interaction system.